Variation of antimetabolite sensitivity with different carbon sources in Bacillus subtilis - Chaudhuri, A; Mishra, A K; Nanda, G (Folia microbiologica, 1982)
The susceptibility of Bacillus subtilis to amino acid analogues was found to be markedly influenced by the carbon source used in the test media. Thialysine inhibited the bacterium with a greater number of carbon sources than the other two analogues tested. 5-Hydroxylysine was inhibitory with glycerol, lactose, D-xylose, L-arabinose and soluble starch while ethionine showed toxicity with lactose, D-xylose and L-arabinose. None of these analogues were toxic at the levels tested when D-galactose was used as carbon source. The bacterium was not susceptible to thialysine with glycerol, to 5-hydroxylysine with L-arabinose and to ethionine with lactose.
Keywords: Ethionine; Bacillus subtilis; cystein; Mannitol; maltosa; arabinosa; Glycerol; Arabinose; ethionin; mannitol; glukosa; Cysteine; metabolismus sacharidů; Glucose; Hydroxylysine; hydroxylysin; glycerol; Maltose; Carbohydrate Metabolism